Continuous spinal anesthesia for lower limb surgery in patient with poor left ventricular function - Mohamed, Rozilah @ Abdul Hadi; Md Ralib, Azrina; Lukman, Mohd Fahmi; Abdullah, Nor Zamzila; Osman, Ariff; Mat Nor, Mohd Basri (Confederation of ASEAN Society of Anaesthesiology, 2009)
Continuous spinal anaesthesia (CSA) has been found to produce good haemodynamic control and prolongation of anaesthetic and analgesic. This is particularly useful in patients with cardiovascular compromise. In contrast to general anaesthesia, CSA allow us to communicate with the patient throughout the operation and thus give us information regarding their degree of anaesthesia and analgesia. By intermittent administration of small doses of local anaesthetic through spinal catheter in CSA, the spread of the block can be better regulated and the risk of abrupt decreases in arterial pressure can be reduced as compared to a single-shock spinal anaesthesia. We reported the use of Pajunk IntraLong ® 21G cannula and 25G spinal microcatheter with 2.5mg of 0.5% heavy bupivacaine in a 59-year-old man with history of diabetes mellitus, hypertension, ischaemic heart disease and poor left ventricular function who had undergone a lower limb surgery. A special technique was introduced during the insertion of microcatheter by slipping it in between a cut-gauze to reduce kinking which is the most common problem encountered during the procedure. The CSA had successfully provided adequate anaesthesia and analgesia to the patient as well as providing haemodynamic stability throughout the operation. From this case we learned that CSA can be offered as an anaesthetic technique with good haemodynamic control in patient with poor left ventricular function. Our technique also offers an alternative method to reduce kinking of the microcatheter to minimize catheter blockade.